COLLABORATIVE SUPPLY CHAIN RESILIENCE FOR MSMEs: A FRAMEWORK FOR INFORMATION SHARING, FLEXIBILITY, AND CONTINUITY - Wawan Ichwanudin; Fitriana (Journal of Jabar Economic Society Networking Forum, 2025)
This conceptual paper develops an integrative framework for collaborative supply chain resilience in micro, small, and medium enterprises (MSMEs). It synthesizes established literature on the resource-based view, dynamic capabilities, organizational learning, absorptive capacity, social capital, resilience, and entrepreneurial ecosystems. The analysis explains how supplier collaboration, information sharing, sourcing flexibility, continuity planning, and relationship governance can be organized into proportionate managerial routines. No primary survey, interview, experimental, or statistical data are claimed. The framework proposes diagnosis, capability mapping, bounded experimentation, evidence review, governance, resource reconfiguration, and learning retention as a cumulative cycle. Implications are developed for owner-managers, support institutions, and future empirical research.